Chilaiditi's syndrome demonstrated by SPECT/CT - Nalini S Perumal; Mboyo-Di-Tamba H Vangu; Khushica Purbhoo; Shireen Dhoodhat (South African Journal of Radiology, 2009)
Purpose: Chilaiditi’s syndrome is a rare condition commonly diagnosed as an incidental radiological finding. The aim of this report is to show the role of SPECT-CT in this syndrome and state the functional and anatomical role of this hybrid imaging modality. Materials and Methods: A case report. Results: A 49-year-old female patient was referred for gallium-67 citrate for a possible granulomatous myositis and underwent SPECT-CT of the abdomen to assess the area of decreased gallium uptake on planar images of the liver. The combined SPECT and CT modality demonstrated findings consistent with the clinical evidence of Chilaiditi’s syndrome. The anatomical part of this hybrid modality made it easier to evaluate the area of gallium lack of uptake which was due to air in the colon. Conclusion: This case does not only show the role of SPECT-CT in this syndrome but also suggest that the use of such modality should be considered whenever available in the evaluation of patients in whom the localization of active disease becomes imperative.